2021
DOI: 10.3892/etm.2021.9765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neutron radiation on Nrf2‑regulated antioxidant defense systems in rat lens

Abstract: Accumulating evidence suggests that ionizing radiation (IR)-induced cataract may be associated with oxidative stress. Nuclear factor erythroid 2-related factor 2 (Nrf2) serves as a master regulator of the antioxidant defense system against oxidative stress. The present study aimed to investigate the effects of different doses of neutron radiation on the Nrf2-reegulated antioxidant defense system in rat lens and assess the status of oxidative stress. A total of 24 SD rats were randomly divided into the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…The lens is one of the most radiosensitive tissues in the human body, and it is known that ionizing radiation can induce cataract, which is ranked second among occupational diseases associated with radiation in China [ 27 ]. Our previous study showed that IR-induced cataract is related to the incapacity of Nrf2 antioxidative systems in the lens [ 13 ]. Enhanced oxidative stress and decreased antioxidant defensive capacity are thought to be the two main contributors to the pathogenesis of cataract [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lens is one of the most radiosensitive tissues in the human body, and it is known that ionizing radiation can induce cataract, which is ranked second among occupational diseases associated with radiation in China [ 27 ]. Our previous study showed that IR-induced cataract is related to the incapacity of Nrf2 antioxidative systems in the lens [ 13 ]. Enhanced oxidative stress and decreased antioxidant defensive capacity are thought to be the two main contributors to the pathogenesis of cataract [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 signal pathway is highly associated with oxidative stress in the lens [ 13 , 42 ]. Nrf2 has been proved to be maintained at a low level through 26S proteasome-mediated degradation and Keap1-mediated ubiquitylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They received a single dose of 10 Gy whole-body γ-radiation at a rate of 1.38 Gy/min. The γ-radiation dose was determined based on our previous study about the effect of neutron radiation on rat lens and Nrf2 signal pathway, and the biological effect of 3.6 Sv neutron radiation is equivalent to 10 Gy γ-radiation [12] . The FA dose was determined according to previous literatures [15][16] .…”
Section: Materials and Methods Ethical Approvalmentioning
confidence: 99%
“…One of the most crucial defenses against oxidative stress is the antioxidative system controlled by nuclear factor erythroid-2 related factor (Nrf2) [11] . In a previous study, we discovered that IR-induced cataract is associated with a dysfunctional Nrf2 antioxidative system in the lens [12] . Together, these suggest that activating the Nrf2 signal pathway might be a way to attenuate IR-induced lens injury.…”
Section: Introductionmentioning
confidence: 96%